Pemetaan Potensi Wisata Berbasis Cerita Rakyat Melalui Komunikasi pemasaran Sebagai Upaya Mendukung Promosi Cultural Tourism di Kabupaten Ogan Komering Ulu - Marini, Marini; Azizah Alhadi, Izzah; Novriansyah, Novriansyah; Jelita Pembayun, Ratu (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2024)
Tourist attractions are part of regional potential that can be used as a promotional event for cultural tourism. Of the many tourist attractions in Ogan Komering Ulu (OKU) Regency, mapping of tourism potential based on folklore is still not optimal. In fact, many natural tourist attractions contain historical folklore that has developed in local communities since time immemorial. The problem arises because of the many folklore-based tourist attractions, only one or two tourist attractions are known to the public and visited by tourists. Therefore, it is necessary to map tourism potential to revive folklore in the community which is an asset of local wisdom as an effort to boost tourism. Another urgency is that many tourist attractions based on local wisdom are starting to become unattractive to tourists due to lack of promotion, causing these tourist attractions to be empty of visitors, even neglected and ultimately abandoned. Therefore, a marketing communication strategy is needed as an effort to attract the attention of tourists to create a creative economy from tourism. The urgency of this research is in line with the Strategic Plan (Renstra) of the Ministry of Tourism and Creative Economy/ Baparekraf Indonesia 2020-2024 that the development of tourism destinations and the creative economy is a priority.